DESIGN AND FABRICATION OF AN ELECTRICALLY POWERED MAIZE PLANTER - BABATUNDE OLUWAMAYOKUN SOYOYE (Journal of Engineering Studies and Research)
The correct application of production inputs for environmental and agricultural production sustainability is a key to successful production of maize. An electrically powered maize planter was designed and fabricated. Light reflecting optoelectronic field counter capable of detecting free falling object with equivalent or greater than 0.7 mm distance in planter delivery tube was designed and built to monitor seed drop on the planter. The device accurately counted the falling seeds with the planter forward speed of 1.38 m/s and seed delivery tube of 24 mm. The average number of two seeds was discharged per hole.